2011
DOI: 10.2144/000113786
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Selection by High-Throughput Sequencing and Informatic Analysis

Abstract: Traditional methods for selecting aptamers require multiple rounds of selection and optimization in order to identify aptamers that bind with high affinity to their targets. Here we describe an assay that requires only one round of positive selection followed by high-throughput DNA sequencing and informatic analysis in order to select high-affinity aptamers. The assay is flexible, requires less hands on time, and can be used by laboratories with minimal expertise in aptamer biology to quickly select high-affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 13 publications
(13 reference statements)
1
62
0
Order By: Relevance
“…Aptamers are selected from libraries through a repetitive combinatorial process known as SELEX (Systematic Evolution of Ligands by Exponential Enrichment) (160,161). Recent improvements in SELEX technology have considerably accelerated the time in which aptamers can be selected, especially with the introduction of high throughput sequencing, which allows for the identification of high-affinity aptamers in early rounds of selection (162,163). This approach also reduces PCR biases that are introduced in each round of selection (164).…”
Section: Rna Aptamers As Novel Therapeutic For Costimulation Of 41bbmentioning
confidence: 99%
“…Aptamers are selected from libraries through a repetitive combinatorial process known as SELEX (Systematic Evolution of Ligands by Exponential Enrichment) (160,161). Recent improvements in SELEX technology have considerably accelerated the time in which aptamers can be selected, especially with the introduction of high throughput sequencing, which allows for the identification of high-affinity aptamers in early rounds of selection (162,163). This approach also reduces PCR biases that are introduced in each round of selection (164).…”
Section: Rna Aptamers As Novel Therapeutic For Costimulation Of 41bbmentioning
confidence: 99%
“…5) confirmed that the Sigma product contained HSA. This is an important observation because of the continuing widespread use of Sigma thrombin in aptamer research (for example, Lee et al, 2008;Yang et al, 2009;Miyachi et al, 2010;Diculescu et al, 2011;Hoon et al, 2011;Wang et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Many different approaches have been described in the literature to discriminate high-affinity aptamers from undesired background sequences arising from selection biases. These methods include enrichment fold (18), repeating motif (8), and copy number (19,20) analysis. We chose copy number analysis to test our capacity to directly distinguish high-affinity aptamers from background sequences via parallel binding measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional selection techniques depend on the convergence of the aptamer pool toward a relatively small number of sequences, such that consensus motifs can be obtained from a few hundred sequences. NGS can analyze millions of sequences, thus identifying enriched sequences much earlier in the selection process; this reduces the number of selection rounds required, and enables the identification and elimination of artifacts that typically arise over repeated rounds of PCR or during the cloning process (18)(19)(20). Despite these advances, the generation of high-quality aptamers remains a time-consuming and low-throughput process.…”
mentioning
confidence: 99%